2001
DOI: 10.1086/501869
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Tuberculin Reactivity in Two General Hospitals in Mexico

Abstract: Although the studied population has a high baseline prevalence of tuberculosis infection and high coverage of BCG vaccination, nosocomial risk factors associated with PPD reactivity were identified as professional risks; strict early preventive measures must be implemented accordingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 21 publications
1
22
1
2
Order By: Relevance
“…Increasing age and duration of employment in the health-care facility (indicating longer cumulative exposure), were associated with higher prevalence of LTBI in most studies (Table 2). The prevalence of LTBI in HCWs increased by 1.04 times (95% CI 1.02 to 1.07) with each additional year of increase in age [26,31], and by 1.5 (95% CI 1.0 to 2.2) [23] to 2.4 (95% CI 1.1 to 5.0) [31] times with employment duration of more than 1 y. The prevalence of LTBI was 3-fold higher [28] with ≥10 y of employment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Increasing age and duration of employment in the health-care facility (indicating longer cumulative exposure), were associated with higher prevalence of LTBI in most studies (Table 2). The prevalence of LTBI in HCWs increased by 1.04 times (95% CI 1.02 to 1.07) with each additional year of increase in age [26,31], and by 1.5 (95% CI 1.0 to 2.2) [23] to 2.4 (95% CI 1.1 to 5.0) [31] times with employment duration of more than 1 y. The prevalence of LTBI was 3-fold higher [28] with ≥10 y of employment.…”
Section: Resultsmentioning
confidence: 99%
“…As seen in Table 3, the prevalence of LTBI among nurses ranged from 43% to 87%. It was reported in eight studies that the prevalence of LTBI in nurses was higher than that in other HCWs (ranging from being 1.3% higher [22] to 35.6% higher [31]. One study, however [32], reported a lower prevalence in nurses, compared to other HCWs).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies investigating the risk of physicians did not indicate an increased infection risk for physicians (Schablon et al, 2009).Other researchers reported a prevalence of LTBI in nurses; a subgroup with high level of patient contact, and thus potential exposure to TB cases (Joshi et al, 2006;Yanai et al, 2003;Garcia-Garcia et al, 2001). …”
Section: Discussionmentioning
confidence: 97%